Parental loss during young adulthood and the experience of seeking social support - Katrín Eva Einarsdóttir 2002- (2024)
Losing a parent to death is one of the most difficult life experiences a person can go through. Individuals who lose a parent at a young age are at greater risk of developing various mental problems. Having a good support system can have a big impact on how the person reacts to the death and heals from it. This qualitative study aimed to explore the experience of individuals in Iceland who lost a parent during young adulthood in seeking social support following the loss. Semi-structured interviews were conducted with five parentally bereaved individuals, and the data were analyzed using reflexive thematic analysis. The results showed that the participants found seeking support from a support group helpful, making them feel like they were not alone. Still, all participants expressed that they needed more support than they received. There was, however, a lack of general information after the participants´ parents died, as they did not receive sufficient advice on where to seek support following the loss. These findings suggest that parentally bereaved young adults experience a lack of social support, which can be hurtful to them. Moreover, there is a need for wider dissemination of information on available support resources in Iceland for those coping with parental loss. Keywords: Parental loss, young adulthood, social support, grief, qualitative research. Að missa foreldri er ein af erfiðustu lífsreynslu sem einstaklingar geta gengið í gegnum. Einstaklingar sem missa foreldri á ungum aldri eru í aukinni hættu á að þróa með sér ýmis geðræn vandamál. Að hafa góðan félagslegan stuðning getur haft mikil áhrif á hvernig einstaklingur bregst við fráfallinu. Markmið þessarar eigindlegu rannsóknar var að skoða reynslu einstaklinga á Íslandi sem misstu foreldri á yngri fullorðinsárum að leita félagslegs stuðnings í kjölfar missisins. Hálf-stöðluð viðtöl voru tekin við fimm einstaklinga sem höfðu misst foreldri og gögnin voru í kjölfarið greind með þemagreiningu. Niðurstöðurnar sýndu að þátttakendum fannst gott að leita ...